2011
DOI: 10.1016/j.ultsonch.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol enrichment from ethanol–water mixtures using high frequency ultrasonic atomization

Abstract: The influence of high frequency ultrasound on the enrichment of ethanol from ethanol-water mixtures was investigated. Experiments performed in a continuous enrichment system showed that the generated atomized mist was at a higher ethanol concentration than the feed and the enrichment ratio was higher than the vapor liquid equilibrium curve for ethanol-water above 40 mol%. Well-controlled experiments were performed to analyze the effect of physical parameters; temperature, carrier gas flow and collection height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…As shown in Figures 3 and 4, the swirling curtain dust removal technology covers the processes of gravity settlement, inertial collision, interception and capture, electrostatic capture, Brownian diffusion, condensation and cyclone centrifugal separation. This is consistent with the previous studies [21][22][23].…”
Section: Design Of the Swirling Curtain Dust Collection Devicesupporting
confidence: 95%
“…As shown in Figures 3 and 4, the swirling curtain dust removal technology covers the processes of gravity settlement, inertial collision, interception and capture, electrostatic capture, Brownian diffusion, condensation and cyclone centrifugal separation. This is consistent with the previous studies [21][22][23].…”
Section: Design Of the Swirling Curtain Dust Collection Devicesupporting
confidence: 95%
“…Previous reports have shown that droplet sizes produced by ultrasound from a liquid solution follow a normal distribution. 15,16,28 Yasuda et al 21 reported that at a solute concentration of 0.1 mole fraction, ultrasonic misting resulted in the median droplet diameters of 5.3, 4.4, 4.0, 4.4, and 4.8 μm for methanol, ethanol, 1-propanol, propylene glycol, and glycerol, respectively. This shows that the ultrasoundgenerated mist from various binary solutions produces mist with different median diameters.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, these atomizers are limited by power requirements and sizes, hindering portable use outside hospital settings 16 . In addition, pneumatic atomizers have poor performance in producing aerosol monodispersity or narrowly dispersed aerosols, and ultrasonic atomizers are relatively large, also have limitations on size control, and molecules will be damaged during the ultrasonic atomization process due to the cavitation effect 17 . To avoid cavitation, it is necessary to reduce the power or to operate at higher frequencies where the power required to induce cavitation is lower than that required for the onset of atomization.…”
Section: Introductionmentioning
confidence: 99%
“…There was a consensus that increasing the device frequency can effectively reduce the size of aerosol droplets and satellite droplets, but the frequency value of capillary wave has always been controversial. Nevertheless, there appears to be some controversy surrounding the adoption of the subharmonic frequency proposed by Lang, i.e., the capillary wave frequency f c is one-half of the excitation frequency f , many studies have also cited it to calculate the aerosol size 14 , 17 . This is due to the difficulty of accurately measuring the frequency at which capillary waves vibrate.…”
Section: Introductionmentioning
confidence: 99%